Novel Single Nucleotide Polymorphisms (SNPs) and Genetic Features of the Prion Protein Gene (PRNP) in Quail (Coturnix japonica) - Kim, Yoonhee; Kim, Yong-Chan; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2022)
Prion diseases are fatal, infectious diseases, caused by conformational changes in the form of a prion protein (PrPSc) derived from a normal prion protein (PrPC). Prion diseases have been reported in a wide range of several mammalian hosts; however, birds and chickens have not been reported to have prion diseases and show resistance to experimental prion infection. To date, genetic polymorphisms of the prion protein gene (PRNP) and protein structure of the prion protein (PrP) related to susceptibility to prion diseases have not been investigated in another meat-eating poultry, quail. To identify the genetic polymorphisms of the quail PRNP gene, polymerase chain reaction (PCR) and DNA sequencing were performed with gene-specific primers in 168 quails. In addition, to investigate the effect of nonsynonymous single nucleotide polymorphisms (SNPs) on quail PrP, 4 in silico programs including PROVEAN, PANTHER, SIFT and AMYCO were used. Furthermore, to investigate the genetic relationship of avian PrPs, phylogenetic analysis and multiple sequence alignments were performed using the MEGA X program. Finally, secondary and tertiary structures of avian PrPs were analyzed by SWISS-model and PDB Viewer programs. We identified 33 novel polymorphisms of the quail PRNP gene including 3 novel nonsynonymous SNPs, T19I, V21I and A22S. V21I was predicted to have deleterious effect on quail PrP by SIFT. Nonsynonymous SNPs of the quail PRNP gene did not affect the amyloid propensity, 3D structure or hydrogen bonds of quail PrP. In addition, nonsynonymous SNPs of the quail PRNP gene did not affect the amyloid propensity of avian PrPs. Quail PrP showed a close evolutionary relationship and similar secondary and tertiary structures to chicken PrP compared to duck PrP. To our knowledge, this is the first report on the genetic and structural properties of the quail PRNP gene.